Teachers’ participation in school decision-making and Its relationship to the leadership style of the school leader - Alghamdi, Saeed Ateq (Journal of Educational and Psychological Sciences, 2020)
The study aimed to participate in school decision-making among secondary school teachers in Riyadh from their point of view, and identify the leadership patterns prevailing among the leaders of secondary schools in Riyadh according to the theory of the administrative network of teachers’ opinion. The relationship between the leadership style of the school leader according to the administrative network theory and the participation of teachers in school decision-making, the study used the descriptive survey style ology. The study population consisted of teachers of public secondary schools in Riyadh city.(325) teachers answered the sample of the study which was randomly selected, The results of the study found that the participation in school decision-making (high) among teachers of their opinion and the overall average (3.85), The dominant leadership style among high school leaders in Riyadh is from the teachers’ minds to lead the team with an arithmetic mean (3.91), the second style is halfway leadership with an arithmetic mean (3.76), the third style is social leadership with an arithmetic average (3.64), and the fourth style is the dominated leadership with an average Arithmetic (3.29), in the last order the negative driving style came with an arithmetic average (3.18),There was a positive correlation between teachers’ participation in decision making and each of the following leadership styles: Team Leadership, Social Leadership, Midway Leadership at Significance Level (0.01), and Negative Correlation between Participation in Teachers Decision Making The significance (0.01), the absence of a significant correlation between the participation in decision-making among teachers and the pattern of negative leadership, and in the light of the findings of the study, a number of recommendations and suggestions were made.